2006
DOI: 10.1080/09553000600617189
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of lipid composition of rat thymus during thymic atrophy by whole-body X-irradiation

Abstract: Lipid analysis shows that the thymic atrophy by X-irradiation was accompanied by a significant change in thymic lipids. This in vivo result opens up new vistas of the role of lipids in apoptosis and phagocytosis during thymic atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Previous studies have reported that radiation induces acute thymic atrophy and reduces the total number of thymocytes[18],[19], especially DP thymocytes[4]. Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that radiation induces acute thymic atrophy and reduces the total number of thymocytes[18],[19], especially DP thymocytes[4]. Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
“…A few data on changes in the lipid metabolism in the thymic cells under the action of ionizing radiation vary significantly depending on the dose, irradiation conditions, study periods, etc. (Miras et al 1968, Kolomiytseva et al 1987, Ahlers et al 1992, Kulagina 1997, Park et al 2006). …”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that the thymus is susceptible to whole body irradiation [ 42 , 43 , 44 , 45 ]. We found that the thymus was also sensitive to BLCIR, as demonstrated by atrophy, thymic apoptosis, and abnormal T-cell development in rats receiving BLCIR.…”
Section: Discussionmentioning
confidence: 99%